1994
DOI: 10.1159/000247141
|View full text |Cite
|
Sign up to set email alerts
|

Regional Analysis of Ceramides within the Stratum corneum in Relation to Seasonal Changes

Abstract: We studied the regional variations and seasonal changes of ceramide quantities in the stratum corneum of human skin. In summer, the total lipid amounts extracted from the stripped stratum corneum were highest in the forehead, followed by the chest and upper back, with the lowest level in the sole of the foot. In winter, while the total lipid distribution followed the same trend as that in summer, the absolute amounts slightly decreased, especially in the forehead and chest, as compared with those found in summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 9 publications
4
43
0
Order By: Relevance
“…Rogers et al [24] and Niemenen et al [25] reported that the amounts of the intercellular lipids of the SC decreased in winter. In contrast, Yoshikawa et al [26] did not find any such seasonal change in the ceramide level in the SC of mixed sex healthy young adults.…”
Section: Discussionmentioning
confidence: 79%
“…Rogers et al [24] and Niemenen et al [25] reported that the amounts of the intercellular lipids of the SC decreased in winter. In contrast, Yoshikawa et al [26] did not find any such seasonal change in the ceramide level in the SC of mixed sex healthy young adults.…”
Section: Discussionmentioning
confidence: 79%
“…Skin lipids from the epidermis and seba ceous glands are a permanent research topic in studies dealing with acne and skin barrier function [1][2][3][4][5][6][7], The purpose of our study was to find a new simple, non-invasive technique for sampling and to improve the separation of skin surface lipids, in particular epidermal lipids. The new method is a modification of those described by Melnik [8], Hollmann et al [9] and Melnik et al [10] ( fig.…”
Section: Introductionmentioning
confidence: 99%
“…Yoshikawa et al [13] found in a study with mixed-gender subjects that the absolute amounts of lipids were decreased in winter, whereas the ceramide mass was slightly increased, refl ecting seemingly enhanced keratinization. This study tended to prove that in young adults, the mass of ceramide remains stable even under different sea-sonal conditions, providing maintenance of a water reservoir and barrier function.…”
Section: Winter and Xerosismentioning
confidence: 99%